Bosnia : faking democracy after Dayton - Chandler, David, 1962- (London ; Sterling, Va. : Pluto Press, 2000)
The Afterword to this new edition updates Bosnian developments and adds an analysis of the structures and problems of the international protectorate in Kosovo.
Democratisation -- Dayton and Sovereignty -- Power-Sharing and Multi-Ethnic Administrations -- The Protection of Human Rights -- Political Pluralism -- Building Civil Society -- Assessments -- The External Dynamic of Democratisation.
Includes bibliographical references (pages 216-244) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Bosnia and Herzegovina -- Politics and government -- 1992-; Yugoslav War, 1991-1995 -- Peace; Bosnie-Herzégovine -- Politique et gouvernement -- 1992-; Guerre dans l'ex-Yougoslavie, 1991-1995 -- Paix; 89.40 internal relations of the state: general; HISTORY -- General; POLITICAL SCIENCE -- International Relations -- General; Peace; Politics and government; Bosnia and Herzegovina; Internationaler Konflikt; Militärischer Konflikt; Nationalitätenfrage.; Sicherheitspolitik; Bosnien-Herzegowina.; Föderative Republik Jugoslawien; Kroatien; Serbien <1992-2002>; Bosnien-Herzegowina; Political situation; Democratization; Bosnia; Bosnia and Herzegovina; Yugoslav wars (1989-2001).; Peace treaties; Democracy; Government; Politics; Guerre dans l'ex-Yougoslavie (1991-1995) -- Paix; Bosnie-Herzégovine -- Politique et gouvernement -- 1992- ...; Geschichte 1996-1999.; Since 1992; 1990-2000.